GaSe oxidation in air: from bulk to monolayers - Rahaman, Mahfujur; Rodriguez, Raul D; Monecke, Manuel; Lopez-Rivera, Santos A; Zahn, Dietrich R T (Semiconductor science and technology, 2017)
Two-dimensional (2D) van derWaals semiconductors have been the subject of intense research due to their low dimensionality and tunable optoelectronic properties. However, the stability of these materials in air is one of the important issues that needs to be clarified, especially for technological applications. Here the time evolution of GaSe oxidation from monolayer to bulk is investigated by Raman spectroscopy, photoluminescence emission, and x-ray photoelectron spectroscopy. The Raman spectroscopy study reveals that GaSe monolayers become oxidized almost immediately after exposure to air. However, the oxidation is a self-limiting process taking roughly 5 h to penetrate up to 3 layers of GaSe. After oxidation, GaSe single-layers decompose into amorphous Se which has a strong Raman cross section under red excitation. The present study provides a clear picture of the stability of GaSe in air and will guide future research of GaSe from single- to few-layers for the appropriate development of novel technological applications for this promising 2D material.